From Knowledge To Performance: How Financial Literacy And Fintech Drive MSME Growth In Banda Aceh - Azhary, Riza Aulia (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The expansion of MSMEs in Indonesia is crucial for strengthening the national economy, generating employment opportunities, and reducing poverty. Nevertheless, MSMEs face significant challenges, particularly in financial management, accessing funding, and integrating financial technology. In Aceh, despite a growing number of MSMEs, persistent issues such as low financial literacy, restricted access to financing, and minimal adoption of digital payment systems hinder enhancements in business performance. The rise of fintech, particularly Islamic peer-to-peer (P2P) lending and payment gateways, is expected to provide solutions that enhance the financial performance of MSMEs. The objective of this study is to evaluate the hypothesis and provide evidence concerning the influence of financial knowledge, peer-to-peer (p2p) sharia lending, and payment gateways on the financial performance of micro, small, and medium enterprises in Banda Aceh City. This research employs primary data, specifically through the distribution of questionnaires to MSMEs in Banda Aceh City. The sampling technique utilised in this study is purposive sampling. A total of 96 respondents from MSMEs were sampled for this research. The analytical method employed to test the hypothesis is multiple linear regression analysis. The findings indicate that peer-to-peer (p2p) sharia lending and payment gateways have a positive impact on financial performance, whereas financial knowledge does not demonstrate a positive effect on financial performance.